Evidence of reproductive senescence of released individuals in a reinforced bird population. (November 2017) - Bacon, Léo; Hingrat, Yves; Robert, Alexandre
Abstract: In free-ranging populations, age-dependent variation in fitness related parameters, in particular the pattern of senescence, has major eco-evolutionary implications and potential influence on population dynamics. Despite the recent surge of studies of senescence in the wild, senescence patterns in species for which population dynamics assessments are crucial, such as translocated populations, remain virtually unexplored. Based on a 15-year nest survey of a North-African Houbara bustard population in Morocco, we investigated age variation in the breeding performance of captive-bred females released in the wild. We identified 781 females, from 1 to 10 years of age, on 1094 nests. We examined how age influenced nest initiation date, clutch size, egg volume, daily nest survival and daily brood survival, as well as whether age-dependent patterns varied according to environmental conditions. Most breeding parameters exhibited variation, suggesting an increase in breeding performance with age in young females (those from 1 to 3 years old). In older females (> 7–8 years old), the egg volume and clutch size decreased with age, in concordance with expectations from senescence theories and previous empirical results obtained from captive Houbara bustards. Finally, our analysis uncovered a significant interaction between age and the amount of precipitation prior to the breeding season on clutch size, suggesting differential abilities of females of different ages to increase their breeding investment. Our study suggests that life histories in translocated individuals are not affected by translocation protocols and provides insights for implementing age dependencies in population viability assessments. Highlights: Analysis of age dependent breeding performances of translocated birds Over 1000 nests monitored in 15 years Evidence for senescence in breeding parameters related to physiological processes Link between breeding performances and age is condition dependent. First characterisation of senescence in breeding parameters of released birds